SOME ELEGANT PROOFS IN 2-METRIC SPACE AND G-METRIC SPACE - Phaneendra, T.; Swamy, K. Kumara (Italian Journal of Pure and Applied Mathematics, 2016)
Elegant analytical proofs of some fixed point theorems in 2-metric space and G-metric space are presented through elementary set theoretical notions of real numbers and repeated use of the rectangle inequality of the G-metric, without an appeal to iterations. The unique fixed points obtained are shown to be contractive fixed points in these spaces.